IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG/JASA MELALUI APLIKASI JAWA TIMUR BELANJA ONLINE (JATIM BEJO) DI INSPEKTORAT PROVINSI JAWA TIMUR - Pramudita, Renata Winna; Megawati, Suci (Publika, 2023)
Procurement of goods/services is a fertile field for corruption cases, the majority of corruption cases that occurred mainly in East Java Province involved playing Self-Estimated Prices (HPS) and providers. The Jatim Bejo application is an effort created by the East Java Provincial Government to prevent corruption cases from occurring in East Java Province. The East Java Provincial Inspectorate is a Regional Apparatus that must carry out procurement using this application. The purpose of this study was to analyze the Implementation of the Goods/Services Procurement Policy through the Jatim Bejo application at the Inspectorate of East Java Province. This research uses descriptive qualitative research with a focus on research using Richard Matland's policy implementation model including policy accuracy, implementation accuracy, target accuracy, and environmental accuracy. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the implementation of goods/services procurement through the Jatim Bejo application at the Inspectorate of East Java Province is going well based on indicators of the accuracy of the executor and the accuracy of the target. On indicators of policy accuracy and environmental accuracy, researchers found several obstacles that occurred, namely there were misses in the Budget Execution Document (DPA) and there were providers who were slow to respond to orders, were late in sending goods, and were confused about taxes. The advice that researchers give is to carry out the preparation of the DPA more maturely and to communicate with providers and policy-formulation institutions. Keywords: Implementation, Procurement, Goods/Services, Jatim Bejo.